Deforestation, environmental quality and economic growth in Southeast Asian countries - Temitayo, Sunmonu Olayiwola (2014)
Environmental quality is one of the factors in the sustainable development of any economy. Of the various environmental problems, deforestation has held a special position because it is intertwined with other forms of environmental problems. Unfortunately, more than half of the regressions published since 1992 do not corroborate Environmental Kuznets Curve for deforestation, this has made authors to be unsatisfied with the current literature on deforestation EKC and have called for further developments. Most importantly, the studies undertaking to explain the determinants of deforestation have not been empirically sound. Deforestation determinants are classified to belong to different level categories, however, most studies do not provide this clear picture of the classifications as causes belonging to different level categories are being included in one deforestation model, whereby the result creates confusion over the cause-effect relationships. Considering the increasing trend of the forest area loss and its consequences in Southeast Asia, this research set out to validate the Environmental Kuznets Curve for deforestation, investigate the main cause of deforestation as well as to outline the impact of its underlying factors for seven (7) countries of the Southeast Asian region namely Malaysia, Thailand, Philippines, Indonesia, Vietnam, LAO and Brunei over 1985 to 2010 with the aim of proposing plausible policy recommendations. The methodology in estimating non-stationary heterogeneous panels, the Panel ARDL, proposed by Peseran was adopted. So far, no research has been conducted using the methodology in deforestation for the region. The advancement in the methodology has helped to influence the outcome positively. As per the underlying factors, rural population growth, liberalization policies (through term of trade) and lucrative export prices (agricultural product export value) causes agricultural land expansion to swell. These outcomes is strengthened by the result obtained from the technology variable which shows that increase in yield is as a result of agricultural land expansion. This means that, for the economy to increase output to feed increased population, to enjoy favourable term of trade and high export value, she has to expand land for agriculture, hence deforestation. The impact of the modernization theory through the economic growth variable could be fully ascertained because of the insignificant coefficient of the variable in the main model. Lastly, the estimation outcome validates EKC hypothesis for deforestation. The result obtained in the research does not wholly represent a particular / specific economy within the region, however, an insight into the overall outlook of the region has been observed where-in policy measure has been outlined to guide and channel this region towards curbing excessive agricultural land expansion with the overall goal of ensuring reduction in deforestation, hence enhancing good environmental quality. These policies are improved agricultural technology, enhanced forest protection, forest management power decentralization, off farm employment opportunities, payment for environmental services amongst others.